Identification of New Putative MicroRNAs in Epstein-barr Virus Genome for Medical and Biotechnological Applications - Mohsen Danaeifar (Archives of Advances in Biosciences, 2024)
Introduction: MicroRNAs play important roles in regulating gene expression in animals and plants. Many studies used these genetic elements to up- or down-regulate human gene expression. It has been shown that viral miRNAs can target and regulate not only viral genes but also host genes. To date, 48 miRNAs have been identified in Epstein-Barr virus (human gamma-herpesvirus 4). This virus can invade and reside in many human tissues such as epithelial or immune system cells. In this study, we evaluated a novel method of finding miRNAs in the Epstein-Barr virus (EBV).